Anharmonic effects control interaction of carbyne confined in carbon nanotubes shaping their vibrational properties - Emil Parth; Andrea Corradini; Weili Cui; Davide Romanin; Christin Schuster; Clara Freytag; Lei Shi; Kazuhiro Yanagi; Matteo Calandra; Thomas Pichler (Nature Communications)
Abstract The resonant Raman response is due to electronic and vibrational excitations. Confined carbyne is a novel one dimensional heterostructure consisting of the linear carbon chain and a hosting carbon nanotube in the bulk limit. The resonant Raman fingerprint of confined carbyne comes concomitant with several new features which can neither be assigned to the hosting tube, nor to the linear carbon chain. This identifies the tube-chain system as a true hybrid structure in which the spectrum is usually driven by modifications in the electronic excitations via charge transfer. We show that the electronic structure results from those of the two isolated systems and the spectral modifications are solely due to the anharmonic interactions between the tube and the chain. Our work establishes confined carbyne as the ideal test system to probe anharmonicity in one dimension and its implications on the resonant Raman response.